Stigma measurement in health: a systematic reviewResearch in context - Sara Malone; Lara Counts; Luke Zabotka; Anneliese Williams; Nele Loecher; Kayla Wynja; Gemma Bryan; Robin Tanner; Ana Cáceres-Serrano; Gia Ferrara; Lucia Fuentes; Tharwa Bilbeisi; et al. (EClinicalMedicine)
Summary: Background: Stigma experienced by individuals with disease is a barrier to health-seeking behaviors and outcomes. Our aim was to systematically review how stigma has been defined and measured and identify gaps in approaches to measurement and intervention. Methods: A systematic review was conducted following PRISMA guidelines. Databases were searched for stigma measurement in health through July 2024. 8123 citations were screened. Data on definitions, measurement, psychometrics, and interventions were extracted. PROSPERO: CRD42023433176. Findings: We identified 2267 studies (2605 tools) from 101 countries. 396 (15.2%) tools focused on development and 2369 (91.0%) applied tools. Most tools assessed adults (77.2%). Over 750 stigma tools were identified; many tools were adapted (n = 674) or shortened (n = 446). 117 studies reported effective interventions, primarily in adults. Key gaps included lack of consensus on definitions, limited pediatric-focused research, and insufficient attention to structural drivers of stigma. Interpretation: This review calls for standardized, context-sensitive stigma measurement and interventions applicable across conditions and settings. Addressing these gaps is crucial to reducing the global burden of stigma and enhancing health outcomes. Future research should focus on unified conceptual approaches and definitions to develop globally adaptable tools and scalable interventions that address both the experiences and structural drivers of stigma. Funding: Components for the programs involved in this work have been funded by St. Jude Children's Research Hospital, the National Cancer Institute (3POCA021765-44S2), the American Lebanese Syrian Associated Charities, and Siteman Cancer Center. The views in this paper are those of the authors and don’t necessarily reflect the funding agencies. The funding agencies were not involved in the writing or submitting of this work.